Effects of alloying composition on the microstructures and mechanical properties of Mg-Al-Zn-Ca-RE magnesium alloy. (January 2019) - Wang, Fang; Xiao, Wenlong; Liu, Maowen; Chen, Jing; Li, Xiang; Xi, Jiabing; Ma, Chaoli
Abstract: With the purpose of increasing our understanding of the microstructural evolution and mechanical properties of Mg-Al-Zn-Ca-RE system alloy, Mg- x Al-(8- x )Zn-4Ca and Mg- x Al-(8- x )Zn-3Ca-1RE (wt. %) casting alloys were studied in this paper. The α-Mg dendrite was refined, and the intermetallic compounds became finer and less divorced by increasing the Al content. During solidification RE addition consumed Al and Zn to form RE-containing phase in the initial solidification stage, and then the residual liquid solidified to form Ca-containing phase without RE participation. The majority phases, Al11 RE3 and C36, were transformed into Al2 REZn2 and Ca2 Mg6 Zn3 as the Al content was decreasing. The Ca-containing phases tended to form a highly interconnected network which would deteriorate the ductility, while the substitution of RE for a part of Ca would make the structure less continuous. A range of eutectic morphologies were found in Ca-containing phases. C36 phase could shape a lamellar eutectic structure, and Ca2 Mg6 Zn3 phase was prone to exhibit as a divorced morphology. Besides, Ca2 Mg6 Zn3 formed at a relatively low temperature which will bring about microshrinkage. Mg-6Al-2Zn-3Ca-1RE alloy containing refined and more evenly distributed C36 with less continuous morphology showed the best mechanical performance. Highlights: Mg- x Al-(8- x )Zn-4Ca and Mg- x Al-(8- x )Zn-3Ca-1RE alloys were prepared by gravity casting. The category, size, morphology and distribution of eutectic phase were affected by the alloying composition. C36 formed instead of Ca2 Mg6 Zn3 with the increase of Al content, which was finer and more evenly distributed. Replacing a part of Ca by RE could modify the microstructure; thus Mg-6Al-2Zn-3Ca-1RE had the best mechanical property.